India 2018: a reference annual - India. Ministry of Information and Broadcasting. New Media Wing (New Delhi Publications Division, 2018)
The reference book is an authoritative compilation of the complete information about the current affairs of the country, which includes important dignitaries, state policy, public schemes and important data related to demographics, trade, economy and others.
Keywords: Economic Development of India -- Infrastructure and Skilled Labor